The prospects for European railways : is the second railway age still here or yet to begin? - Givoni, M; Holvad, T (Alexandrine Press, 2009)
Transport technologies seldom make a comeback, save in nostalgia trips for well-heeled tourists. Stagecoaches have not made a reappearance on the Bath Road, nor sedan chairs on the streets of London. But there is a spectacular exception: railways, written off thirty years ago as a Victorian anachronism destined to atrophy before the steady growth of motorway traffic, have suddenly become one of the basic technologies of the twenty-first century. The reason of course is the high-speed train.